Family history density of substance use problems among undergraduate college students: Associations with heavy alcohol use and alcohol use disorder. (August 2017) - Powers, Gregory; Berger, Lisa; Fuhrmann, Daniel; Fendrich, Michael
Abstract: Purpose: A family history of alcoholism has been found associated with problematic alcohol use among college students, but less research has examined the effects of family history density of substance use problems in this population. This study examined the prevalence of family history density of substance use problems and its associations with heavy alcohol use, negative alcohol consequences, and alcohol use disorder in a college sample. Methods: Based on a secondary analysis of a probability sample, data were analyzed from 606 undergraduate students. Family history density of substance use problems included both first and second degree biological relatives. Heavy alcohol use was the total number of days in which participants drank five/four or more drinks for men/women, negative alcohol consequences were derived from items commonly asked in college student surveys, and an alcohol use disorder was defined as meeting diagnostic criteria for alcohol abuse or dependence. Point prevalence estimated rates of family history density of substance use problems, and negative binomial, ANCOVA, and logistic regression models examined associations between family history density and the alcohol variables while adjusting for sociodemographic variables. Results: Family history density of substance use problems was not significantly associated with total days of heavy alcohol use. Having a second degree, a first degree, or both a first and second degree relative(s) with a substance use problem, however, was significantly associated with experiencing negative alcohol consequences. In addition, having both a first and second degree relative(s) with a substance use problem significantly increased the odds of having an alcohol use disorder. Conclusions: Family history density of substance use problems may play a role in experiencing negative alcohol consequences and in having an alcohol use disorder among undergraduate college students and may be an important risk factor to assess by college health professionals. Highlights: Family history density of substance use problems was examined for associations with college drinking and outcomes. No association was found between family history density of substance use problems and total number of heavy drinking days. Only those reporting first and second degree relative(s) were more likely to be assessed as having an alcohol use disorder.